2014
DOI: 10.1038/onc.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in ERK activity as visualized by in vivo FRET imaging of mammary tumor cells developed in MMTV-Neu mice

Abstract: Human epidermal growth factor receptor2/Neu, which is overexpressed in about 30% of human breast cancers, transduces growth signals in large part via the Ras-Raf-MEK-ERK pathway. Nevertheless, it is a matter of controversy whether high ERK activity in breast cancer tissues correlates with better or worse prognosis, leaving the role of ERK activity in the progression of breast cancers unresolved. To address this issue, we live-imaged ERK activity in mammary tumors developed in mouse mammary tumor virus-Neu tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…While ERK activation is widely regarded as pro-tumourigenic, it was recently shown to inversely correlate with stem cell self-renewal in mammary tumours36 and with the maintenance of stem cell identity in mouse intestine37. Also noteworthy in this context, activation of the STAT3 pathway by IL6 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…While ERK activation is widely regarded as pro-tumourigenic, it was recently shown to inversely correlate with stem cell self-renewal in mammary tumours36 and with the maintenance of stem cell identity in mouse intestine37. Also noteworthy in this context, activation of the STAT3 pathway by IL6 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Johnsson et al visualized Rac1 signaling during disease development in multiple organs using Rac1-FRET mice (21). Kumagai et al revealed that breast cancer cells with low ERK activity possess cancer stem-cell-like properties by isolating the cells depending on the FRET efficiency from MMTV-Neu:Eisuke mice, a transgenic mouse line expressing the ERK FRET biosensor (36). And in this work, we focus on an example of intravital imaging with the EKAREV-NLS FRET biosensor, which successfully resolved an urgent question about drug resistance in cancer treatment.…”
Section: Application To Intravital Imagingmentioning
confidence: 97%
“…Similarly, the Erk and PAK-FRET biosensor mice have permitted us to untangle the molecular mechanisms governing extracellular signal transduction, proliferation, and differentiation in vivo (14)(15)(16). Interestingly, the Erk FRET mouse has recently been used to study Erk activity in distinct subpopulations of breast cancer cells to monitor chemotherapy pharmacokinetics in breast cancer (17). FRET biosensors are, therefore, an emerging preclinical tool for cancer research and help us probe dynamic events in vivo rather than the current in vitro static and fixed endpoints discussed earlier.…”
Section: Discussionmentioning
confidence: 99%